A New Class of Tunable Dendritic Diphosphine Ligands: Synthesis and Applications in the Ru‐Catalyzed Asymmetric Hydrogenation of Functionalized Ketones. Issue 32 (10th July 2014) - Ma, Baode; Miao, Tingting; Sun, Yihua; He, Yanmei; Liu, Ji; Feng, Yu; Chen, Hui; Fan, Qing‐Hua
Abstract A series of tunable G0–G3 dendritic 2, 2′‐bis(diphenylphosphino)‐1, 1′‐binaphthyl (BINAP) ligands was prepared by attaching polyaryl ether dendrons onto the four phenyl rings on the P atoms. Their ruthenium complexes were employed in the asymmetric hydrogenation of β‐ketoesters, α‐ketoesters, and α‐ketoamides to reveal the effects of dendron size on the catalytic properties. The second‐ and third‐generation catalysts exhibited excellent enantioselectivities, which are remarkably higher than those obtained from the small molecular catalysts and the first‐generation catalyst. Molecular modeling indicates that the incorporation of bulky dendritic wedges can influence the steric environments around the metal center. In addition, the ruthenium catalyst bearing a second‐generation dendritic ligand could be recycled and reused seven times without any obvious decrease in enantioselectivity.